PENGARUH MACAM DAN DOSIS PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCHOY (Brassica rapa L.) - Ahmad Sofian; Yekti Maryani; Lilik Kusdiarti (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to determine the effect of kinds and dosage of manure application on the growth and yield of pakchoy. The experiment was conducted in a the field of Merapi Organic Farm, located in Balangan Wukirsari village, Cangkringan, Sleman Yogyakarta. The altitude is 500 meters above sea level with temperature of 23 0C - 29 0C and regosol soil type. This research was conducted in October through December 2016. The experiment was a factorial 2 x 3 and one control, arranged in a randomized complete block design. The treatment consists of two factors, the first factor consists of two kinds: namelyÂ vermicompost and cow manure. The second factor is the dose of organic manure: 5 ton, 10 ton and 15 ton per hectare. Each treatment was repeated three times. Variables observed were plant height, leaf number, leaf area, plant fresh weight, root fresh weight, dry weight of plants, root dry weight and yield per hectare. The analysis showed that no interaction effect between the two factors on the growth and yield. Various kinds and dose ofÂ manure showed no significant effect on the growth and yield, per hectare. The application of manure significantly affected plant height and plant fresh weight.